2017
DOI: 10.1016/j.str.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Active-Site Flexibility and Substrate Specificity in a Bacterial Virulence Factor: Crystallographic Snapshots of an Epoxide Hydrolase

Abstract: Summary The CFTR inhibitory factor (Cif) is an epoxide-hydrolase virulence factor from Pseudomonas aeruginosa, with catalytic activity that perturbs essential host-defense networks. Its targets are largely unknown, but include an epoxy-fatty acid. In this class of signaling molecules, chirality can be an important determinant of physiological output and potency. Here we explore the active-site chemistry of this two-step α/β-hydrolase and its implications for an emerging class of virulence enzymes. In combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 57 publications
6
13
0
Order By: Relevance
“…In this study, decreased volume of stereo-selective pocket correlates with increased stereo-selectivity. Enzyme selectivity also depends on the active site flexibility, wherein a less flexible site is more selective [66]. All these results are in line with our rational approach which results in DM-GTL with excellent fatty acid selectivity.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, decreased volume of stereo-selective pocket correlates with increased stereo-selectivity. Enzyme selectivity also depends on the active site flexibility, wherein a less flexible site is more selective [66]. All these results are in line with our rational approach which results in DM-GTL with excellent fatty acid selectivity.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, decreased volume of stereo-selective pocket correlates with increased stereo-selectivity. Enzyme selectivity also depends on the active site flexibility, wherein a less flexible site is more selective [67]. All these results are in line with our rational approach in designing the DM-GTL.…”
Section: Discussionsupporting
confidence: 84%
“…This proposed critera is based, in part, on the concept of 'near attack conformers' [266,267], which is used as a predictor of the enantioselective potential of mutants in a number of studies [268,269,46,47]. The criteria used by Reetz et al [252], however, does not account of the possibility of mixed or alternative regioselectivity that may occur in EH reactions [29] (discussed further in Chapter 7). Here a more comprehensive set of distance criteria are applied, specifically optimal poses for both enantiomers are ranked by the distances between Asp192Oδ 1:C-1, Asp192Oδ 1:C-2, Asp192Oδ 2:C-1 and Asp192Oδ 2:C-2.…”
Section: Analysis Of Docking Resultsmentioning
confidence: 99%
“…The mean distances between Asp192Oδ 1 and Oδ 2 to both C-1 and C-2 are similar for both enantiomers, suggesting the possibility of a lack of regioselectivity. A lack of regioselectivity is supported by a recent study where ester intermediates were covalently linked to the EH from Pseudomonas aeruginosa and successfully trapped and crystallised [29]. The study demonstrated that the enzyme could potentially attack a distinct carbon atom on the epoxide moiety of each enantiomeric pair of the substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation